2007
DOI: 10.1002/app.27358
|View full text |Cite
|
Sign up to set email alerts
|

Attapulgite@polymer particles with double‐layer polymer shell via soapless seeded emulsion polymerization

Abstract: Attapulgite needle encapsulated with doublelayer polymer shell (ATP@DP) were prepared by the soapless seeded emulsion polymerization of the second monomer styrene in the dispersion of the attapulgite needle encapsulated with poly(methyl methacrylate) (ATP@PMMA), which was also conducted by the soapless seeded emulsion polymerization of the first monomer methyl methacrylate with the cetyltrimethylammonium bromide (CTAB) modified attapulgite needle (org-ATP) as seeds. The different morphologies of ATP, ATP@PMMA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…1. The particles are approximately 20 nm in diameter, the length is from several hundred nanometers to several micrometers, and it has high temperature endurance and high surface area [21]. There are large reserves of ATP in South China (Jiang Su, Zhe Jiang, and An Hui provinces) and in the USA (Florida), although ATP has been mainly used as absorbent, catalyst carrier for the applications in various catalytic reactions, densifying agent, adhesive, food additive and a filler, etc [22].…”
mentioning
confidence: 99%
“…1. The particles are approximately 20 nm in diameter, the length is from several hundred nanometers to several micrometers, and it has high temperature endurance and high surface area [21]. There are large reserves of ATP in South China (Jiang Su, Zhe Jiang, and An Hui provinces) and in the USA (Florida), although ATP has been mainly used as absorbent, catalyst carrier for the applications in various catalytic reactions, densifying agent, adhesive, food additive and a filler, etc [22].…”
mentioning
confidence: 99%
“…However, ATT has a larger length/diameter ratio relative to PS particles, which have an average particle size of approximately 90–85 nm, as seen in TEM images. Therefore, the monomer-encapsulated ATT latex claimed by Liu et al was not established in our system. Furthermore, the general purpose of the pretreatment of the ATT needles with surfactants was to introduce the organic chains onto the ATT needle surfaces so they had more affinity for the monomers, thereby facilitating encapsulation.…”
Section: Resultsmentioning
confidence: 96%
“…Attapulgite clay (ATT) is a kind of needle-shaped silicate. The particles are 20 nm in diameter, and the length can be from several hundred nanometers to several micrometers. , Recently, there have been several studies describing the preparation of PNCs using ATT. For example, Shen et al successfully synthesized polyamide-6 (PA6)/ATT nanocomposites via in situ polymerization, in which ATT was modified with cetyltrimethylammonium bromide (CTAB) and toluene-2,4-diisocyanate (TDI). The microscopic results showed that the ATT particles were well-dispersed in the PA6 matrix on a nanometer scale and formed an “exfoliated” morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation